Faktor-faktor yang Mempengaruhi Jumlah Pengangguran di Provinsi Bali - Senet, Dyah Rahadi; Yuliarmi, Ni Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2014)
After the Bali bombing which resulted in the Termination of Employment ( FLE) experienced by the majority of people who work in the tourism sector . This is also indicated by the presence of unemployment in Bali which is dominated by young people . This condition can worsen the social and economic problems. This study aimed to examine the effect of the level of investment , economic growth , inflation and population growth simultaneously and partially on the number of unemployed in the province of Bali in 1986-2012 . The data is secondary data obtained from BPS and BKPMD Bali Province . Data analysis techniques in this study using the technique of multiple linear regression analysis . The analysis showed that the variables of economic growth and inflation is negative and significant effect on the number of unemployed in the province of Bali . Variable population growth and a significant positive impact on the number of pengangangguran in Bali Province . While the investment rate does not affect significantly the number of unemployed in the province of Bali.
Keywords: Investasi; Pertumbuhan Ekonomi; Inflasi; Pertumbuhan Penduduk; Pengangguran